2022
DOI: 10.1007/s12078-022-09304-y
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Mouthfeel and Temperature Alterations in COVID-19 Patients Six to Ten Months After Diagnosis

Abstract: Introduction The characteristics and impact of mouthfeel, temperature, smell, and taste alterations in patients with COVID-19 at a long term are yet not well known. In this study, these characteristics and their impact on daily life and quality of life (QoL) were assessed, six to ten months after infection, in patients with COVID-19 searching for peer support on Facebook. Methods Between December 2020 and January 2021, members of two COVID-19 Facebook grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Additionally, the intensity of astringency was rated as lower in PROP non-sensitive subjects according to gender [ 50 , 51 ] which are known to have lower density of fungiform papillae in the anterior two-thirds of the dorsal tongue surface and lower taste sensitivity compared to the sensitive phenotype [ 52 , 53 ]. In a recent study on a group of COVID-19 patients, 85% of whom reporting a taste impairment, showed expressed alteration also in mouthfeel and temperature sensation in 58% and 25% of them, respectively [ 54 ]. Furthermore, in this study patients had a lower identification score for low concentration of capsaicin-evoked sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the intensity of astringency was rated as lower in PROP non-sensitive subjects according to gender [ 50 , 51 ] which are known to have lower density of fungiform papillae in the anterior two-thirds of the dorsal tongue surface and lower taste sensitivity compared to the sensitive phenotype [ 52 , 53 ]. In a recent study on a group of COVID-19 patients, 85% of whom reporting a taste impairment, showed expressed alteration also in mouthfeel and temperature sensation in 58% and 25% of them, respectively [ 54 ]. Furthermore, in this study patients had a lower identification score for low concentration of capsaicin-evoked sensation.…”
Section: Discussionmentioning
confidence: 99%